Integrative perspective of intervention in the formation of reflective thinking in a teenager - González-Moreno, Claudia Ximena (IE Revista de Investigación Educativa de la REDIECH, 2025)
The objective of this article is to identify the effect of an intervention with an integrative perspective among historical-cultural psychology, the educational field and the family in the formation of reflective thinking in a 14-year-old adolescent from the city of Bogotá. For the intervention, the experimental formative method proposed by Vygotsky was used. The program was designed based on the proposals of the historical-cultural conception of communication activity, shared dialogue in the reading of picture books and psychological development, under a methodological design of pre-test and post-test. It is concluded that reflective thinking, by transforming actions from external to internal, enables the development of social, emotional and learning skills in adolescents. This means that the intervention has effects on the moral conscience of adolescents, that is to say, the integrative perspective allows the development of a responsible personality because it enables them to assume the consequences of their actions and reflect before acting.